Associative model proposal for the internationalization of the small and medium agribusiness agricultural companies of the Tacna Region, 2016. - Delgado Kuong, Luis Miguel (2019)
Objective: focused on formulating a proposal for an associative model for the commercialization and internationalization of small and medium agroindustrial olive companies of the Tacna Region in 2016. Methodology: non-experimental, relationship and proactive study. Population: 50 entrepreneurs and companies’ Main results: the diagnosis of the agroindustrial activity of the small and medium agro-industrial olive companies of the Tacna Region is favorable (MEFE Matrix = 3.23, MEFI Matrix = 3.69). Conclusion: the proposal of an associative model for the marketing and internationalization of small and medium agroindustrial olive companies of the Tacna Region, is the Group Agro Olive Tacna Cluster that has five axes: Axis 1 Problem identified through a strategic diagnosis; Axis 2 Objectives; Axis 3 Olivícola cluster and internationalization; Axis 4. Success factors and Axis 5. Challenges, because it would generate competitiveness and improve the positioning of the olive in the international market.